Juvenile-Onset Recurrent Respiratory Papillomatosis in the United States, Epidemiology and HPV Types—2015–2020. (19th June 2021) - Amiling, Raiza; Meites, Elissa; Querec, Troy D; Stone, Laura; Singh, Vidisha; Unger, Elizabeth R; Derkay, Craig S; Markowitz, Lauri E
Abstract : Among 215 US children with juvenile-onset recurrent respiratory papillomatosis in 2015–2020, most were firstborn children delivered vaginally to young mothers; most mothers reported no human papillomavirus (HPV) vaccination before delivery. Vaccine-preventable HPV types were detected in almost all papilloma specimens tested. Abstract: Background: Juvenile-onset recurrent respiratory papillomatosis (JORRP) is a rare disease characterized by the growth of papillomas in the respiratory tract. In the United States, JORRP is not a nationally notifiable condition and current data are limited. Methods: Children with JORRP aged <18 years were enrolled from 26 pediatric otolaryngology centers in 23 US states from January 2015 through August 2020. Demographic, birth information, and maternal vaccination history were collected from a parent/guardian. Clinical history was abstracted from medical records. Papilloma biopsies were tested for 28 human papillomavirus (HPV) types. Mothers who delivered in 2006 or later were considered age-eligible for HPV vaccination if aged ≤26 years in 2006. We described characteristics of enrolled children and their birth mothers and analyzed disease severity by diagnosis age and HPV type using multiple logistic regression. Results: Among 215 children with JORRP, 88.8% were delivered vaginally; 64.2% were firstborn. Among 190 mothers, the median delivery age was 22 years. Among 114 (60.0%) age-eligible for HPV vaccination, 16 (14.0%) were vaccinated, 1 (0.9%) before delivery. Among 162 specimens tested, 157 (96.9%) had detectable HPV; all 157 had a vaccine-preventable type. Disease severity was associated with younger diagnosis age and HPV 11; adjusted analyses found only younger diagnosis age significant (adjusted odds ratio: 6.1; 95% confidence interval: 2.9, 12.8). Conclusions: Children with JORRP were commonly firstborn and delivered vaginally to young mothers; most of the mothers reported no HPV vaccination before delivery. Vaccine-preventable HPV was identified in all specimens with detectable HPV. Increasing preexposure HPV vaccination could substantially reduce or eliminate JORRP in the United States.